Financing Political Parties in Germany – the Case of Political Foundations - Paul, Sebastian (2016)
The thesis analyzes the current German political situation in terms of party financing. In particular, the special role that political foundations play in this connection and what influence they have on German political parties, decision makers and German politics in general, shall be examined. Political foundations are playing an important role in party financing and some of them are even operating internationally. Exactly what role they play is still not well known by the German public and many reports related to this topic do not exist. One of the main concerns of the thesis will consequently be on corruption and lobbying in the German political system.